ACCESSING PUBLIC TRANSPORTATION POLICIES FOR PERSONS LIVING WITH DISABILITIES IN KENYA - Nyaura, Jasper Edward; Ngugi, Margaret Njeri (PEOPLE: International Journal of Social Sciences, 2019)
Despite the fact that the constitution of 2010 has given priority to persons with disabilities with specific focus to bill of right, their right to movement is still curtailed in the public transportation sector system in Kenya. This paper is motivated towards examining the challenges faced by persons with disabilities in accessing public transport in Kenya. This paper is based on desktop research/general review design/methodology. Consequently, the transportation services towards persons with disabilities are lacking. The challenges encountered are that there are no vehicles designated for easier mobility from one point to the other, they plight is not looked at by the public and the private sector and they are not accorded due consideration in the access of the public transport. The paper therefore argues that enough has not been done to enhance transport access for the persons with disabilities. Moreover, there is enhanced systematic implementation of vision 2030 towards improved infrastructure throughout the country among other policies by the government. This has aimed at ensuring that there is access of public transportation system to the citizens at large. Therefore, there is need for stakeholder participation including the public and the private sector towards promoting and providing transportation facilities to the persons with disabilities. The recommendations put forward in this paper are geared towards improved access of transportation facilities by persons with disabilities in Kenya.